2020
DOI: 10.1186/s12893-020-00765-0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct fusion intersegmental parameters regarding local sagittal balance provide similar clinical outcomes: a comparative study of minimally invasive versus open transforaminal lumbar interbody fusion

Abstract: Background: Most contemporary studies suggested that intersegmental parameters including disc height and local lordosis contribute to the sagittal balance of fused lumbar. Although similar clinical outcomes following MIS-and Open-TLIF were reported essentially at the early postoperative time, the comparison of local balance variables after these two different techniques was lack. The radiological differences maybe not relevant to the postoperative efficacy at an earlier post-operation stage. But during the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…With the development and advancement of surgical techniques, the applications of minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) have expanded. Several clinical studies have confirmed that MIS-TLIF achieves comparable results to traditional intervertebral decompression and fusion in terms of postoperative clinical efficacy but has the advantages of less bleeding and less soft tissue damage [ 5 , 6 ]. However, there are limited reports of studies related to MIS-TLIF for the treatment of ULDH.…”
Section: Introductionmentioning
confidence: 99%
“…With the development and advancement of surgical techniques, the applications of minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) have expanded. Several clinical studies have confirmed that MIS-TLIF achieves comparable results to traditional intervertebral decompression and fusion in terms of postoperative clinical efficacy but has the advantages of less bleeding and less soft tissue damage [ 5 , 6 ]. However, there are limited reports of studies related to MIS-TLIF for the treatment of ULDH.…”
Section: Introductionmentioning
confidence: 99%